Business Development Strategy for Mechanical Electrical Plumbing Contractor at PT Vastorindo Djaya Semesta - Aditya Eko Purnomo; Raden Dikky Indrawan; Suhendi (Green Publisher Indonesia, 2026)
The mechanical, electrical, and plumbing (MEP) construction industry faces external pressures in the form of tightening infrastructure budgets, price-based tender competition, and the accelerated adoption of digitalisation such as Building Information Modelling (BIM), which demands an increase in contractors' internal capabilities. This study aims to formulate a business transformation strategy for PT Vastorindo Djaya Semesta (PT VDS) as a MEP contractor through a comprehensive analysis of the external-internal environment and an industry foresight approach. The research uses primary data (observations, in-depth interviews, and internal-external expert questionnaires) and secondary data (literature studies). The analysis was conducted through industry foresight, PESTEL and Porter's Five Forces for the external environment, value chain analysis and VRIO for the internal environment, followed by the preparation of IFE–EFE, IE Matrix, and SWOT/TOWS matrices to produce alternative strategies, and priority determination using AWOT (a combination of SWOT and AHP). The analysis results placed PT VDS in Cell V of the IE Matrix (hold and maintain), indicating the need to maintain core performance while selectively strengthening internal capabilities. This study provides priority strategy guidelines that PT VDS can use to strengthen its competitiveness and business sustainability through capability transformation and refinement of its service value proposition in the MEP construction market.